Scope and magnitude of private sector financing and provision of immunization in Benin, Malawi and Georgia. Issue 27 (12th June 2019) - Levin, Ann; Munthali, Spy; Vodungbo, Venance; Rukhadze, Natia; Maitra, Kuhu; Ashagari, Tesfaye; Brenzel, Logan
Abstract: Background: Little is known about the role of private sector providers in providing and financing immunization. To fill this gap, the authors conducted a study in Benin, Malawi, and Georgia to estimate (1) the proportion of vaccinations taking place through the private sector; (2) private expenditures for vaccination; and (3) the extent of regulation. Methods: In each country, the authors surveyed a stratified random sample of 50 private providers (private for-profit and not-for-profit) using a standardized, pre-tested questionnaire administered by trained enumerators. In addition, the authors conducted 300 or more client exit interviews in each country. Results: The three countries had different models of private service provision of vaccination. In Malawi, 44% of private facilities, predominantly faith-based organizations, administered an estimated 27% of all vaccinations. In Benin, 18% of private for-profit and not-for-profit facilities provided vaccinations, accounting for 8% of total vaccinations. In Georgia, all sample facilities were privately managed, and conducted 100% of private vaccinations. In all three countries, the Ministries of Health (MoHs) supplied vaccines and other support to private facilities. The study found that 6–76% of clients paid nominal fees for vaccination cards and services, and a small percentage (2–26%) chose to pay higher fees for vaccines not within their countries' national schedules. The percentage of private expenditure on vaccination was less than 1% of national health expenditures. The case studies revealed that service quality at private facilities was mixed, a finding that is similar to those of other studies on private sector vaccination. The three countries varied in how well the MoHs managed and supervised private sector services. Discussion/Conclusion: The private sector plays a growing role in lower-income countries and is expanding access to services. Governments' ability to regulate and monitor immunization services and promote quality and affordable services in the private sector should be a priority.